СТАНОВЛЕННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ В СИСТЕМІ ВУЗІВСЬКОЇ ПІДГОТОВКИ ВЧИТЕЛІВ ТЕХНОЛОГІЇ (Педагогіка вищої та середньої школи, 2008)
In the article the basic constituents of professional competence of future teachers of technology are examined by introduction to the educational process of the special trainings of seIf-know ledge.